2018
DOI: 10.1016/j.crvi.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic and inorganic sources of nutrients on the functional diversity of microbial communities in the vegetable cropping system of the Indo-Gangetic plains

Abstract: The aim of the present study was to assess the effects of different organic and inorganic fertilizers on the functional diversity of soil microbial community under a vegetable production system. The Biolog Eco-plate technique and indices, such as average well-colour development (AWCD), McIntosh and Shannon diversity were employed to study the diversity of soil microorganisms. The AWCD, i.e. overall utilization of carbon sources, suggested that different organic treatments had a significant impact on the metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…Higher soil aeration was reported to stimulate microbial biomass and change community composition in paddy fields, findings which support the determination of improved microbial biomass, activity, and diversity in the aerated irrigation groups in this study (Figure d and Table ). The differences of microbial metabolic functions in the soil samples were indicated by the utilization of 31 kinds of carbon sources during the Biolog microplate analysis. , The clearly differentiated metabolic function groups between the aerated irrigation group and the control (Figure ) further demonstrated that the oxygenation treatments not only boosted microbial activity but also played a constructive role in increasing functional diversity of soil microbial communities . Even though the microbial metabolic functions (Figure b) were undifferentiated between the normal pump-aerated and nanobubble-aerated irrigation treatments, gene level differences in the soil microbial communities may be significant, which need to be further studied.…”
Section: Discussionmentioning
confidence: 94%
“…Higher soil aeration was reported to stimulate microbial biomass and change community composition in paddy fields, findings which support the determination of improved microbial biomass, activity, and diversity in the aerated irrigation groups in this study (Figure d and Table ). The differences of microbial metabolic functions in the soil samples were indicated by the utilization of 31 kinds of carbon sources during the Biolog microplate analysis. , The clearly differentiated metabolic function groups between the aerated irrigation group and the control (Figure ) further demonstrated that the oxygenation treatments not only boosted microbial activity but also played a constructive role in increasing functional diversity of soil microbial communities . Even though the microbial metabolic functions (Figure b) were undifferentiated between the normal pump-aerated and nanobubble-aerated irrigation treatments, gene level differences in the soil microbial communities may be significant, which need to be further studied.…”
Section: Discussionmentioning
confidence: 94%
“…Organic amendments have been shown to enhance soil food webs by increasing soil microorganisms and reducing plant-parasitic organisms (Treonis et al, 2010). Organic amendments may have differential effects depending on their quality and the type of soil (Pérez-Piqueres et al, 2006;Saison et al, 2006;Bastida et al, 2008) and may strongly affect soil microbial processes and contribute to soil functions and microbial diversity (Ho et al, 2017;Manjunath et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…McIntosh index (U) was calculated according to Manjunath et al [ 46 ]: where N is the number of substrates, OD i , is the corrected OD value of each substrate containing well.…”
Section: Methodsmentioning
confidence: 99%